Cardiovascular Sympathetic Function Status by Cold Pressor Test in Lactating Mothers (Journal of Rangpur Medical College, 2025)
Background: Lactation has a significant impact on women cardiac autonomic control and various cardiometabolic changes which occurs during lactation that influence women health. Objective: The study was aimed to assess the cardiovascular sympathetic functions status by the cold pressor test in lactating mothers. Methods: This cross-sectional analytical study was conducted in the Department of Physiology, Rangpur Medical College, Rangpur from July 2022 to June 2023. After obtaining permission, a total 100 subjects who were met the inclusion criteria and enrolled in the study after briefing them objectives of the study. Among them 50 apparently healthy lactating mothers (Group A) and 50 apparently healthy non-lactating mothers (Group B) were selected through purposive sampling. The evaluation of sympathetic functions in selected individuals was done by cold pressor test. The individuals were selected from Breast Feeding or Lactating Corner, Out Patient Department of Paediatrics. For statistical analysis, unpaired ‘t’ test was performed by computer-based software SPSS-25 version for windows. Results: Resting systolic and diastolic blood pressure was significantly higher (P